2017
DOI: 10.1093/bja/aex317
|View full text |Cite
|
Sign up to set email alerts
|

SmartPilot® view-guided anaesthesia improves postoperative outcomes in hip fracture surgery: a randomized blinded controlled study

Abstract: NCT 02556658.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
0
16
1
3
Order By: Relevance
“…The SmartPilot ® View graphically depicts the interaction of hypnotic and analgesic drugs with isoboles and uses NSRI to measure the depth of anesthesia. Another benefit of SPV is that it displays the current depth of anesthesia as well as the expected level for the next 10 minutes [8,10]. When opioids and intravenous anesthetics are co-administered for anesthesia maintenance, fifty percent probability to tolerate laryngoscopy (TOL 50) is equal to NSRI 50, and ninety percent probability to tolerate laryngoscopy (TOL 90) is equal to NSRI 20.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SmartPilot ® View graphically depicts the interaction of hypnotic and analgesic drugs with isoboles and uses NSRI to measure the depth of anesthesia. Another benefit of SPV is that it displays the current depth of anesthesia as well as the expected level for the next 10 minutes [8,10]. When opioids and intravenous anesthetics are co-administered for anesthesia maintenance, fifty percent probability to tolerate laryngoscopy (TOL 50) is equal to NSRI 50, and ninety percent probability to tolerate laryngoscopy (TOL 90) is equal to NSRI 20.…”
Section: Discussionmentioning
confidence: 99%
“…Leblanc et al [10] examined the effect of SPV on postoperative results in patients undergoing hip fracture surgery compared with standard anesthesia administration, assuming that the use of SPV in older patients may be particularly advantageous. Patients in the SPV group had better postoperative outcomes, including a shorter hospital stay [10]. Although our study showed a reduction in anesthetic consumption, the consequences on patient outcomes, postoperative mortality, and morbidity were not studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Podemos indicar que el uso de noradrenalina en infusión continua demuestra estabilidad en las presiones arteriales medias durante todo el procedimiento quirúrgico. Así Leblanc y col 18 desarrollaron un Software SmarPilot® guiado, que reduce la duración de la hipotensión, las complicaciones postoperatorias y la estancia hospitalaria de los pacientes.…”
Section: Referenciasunclassified
“…SPVguided anesthesia enabled faster recovery of orientation (451 ± 100 s in the control group and 316 ± 57 s in the SPV group). Several similar clinical studies have used PK-PD simulation systems [5][6][7][8]. As these studies have examined the effects of reduced anesthetic use and shortened recovery time as outcomes, the use of PK-PD simulation systems could prevent delayed recovery due to drug accumulation from the clinical viewpoint.…”
mentioning
confidence: 99%